Inventario florístico y estimación de carbono aéreo en la cobertura forestal nativa de la finca Santa Clara, en el cantón Baba 2022 - Echeverria Mera, July Maitte (2023)
Dry forests are threatened by lack of information and protection initiatives. The objective of this research is to know the floristic diversity of Finca Santa Clara, estimate tree biomass and carbon storage. A forest census was carried out in which all individuals with a diameter greater than 10 cm were considered. A total of 47 individuals were recorded, in 10 species and 6 families. The most ecologically important family was Fabaceae. The species with the highest IVI were Erythrina velutina, Cecropia peltata, Albizia guachapelí. The family with the highest IVF was Fabaceae. The altimetric, diametric and basal area classes indicated that class I with DAP (0-10cm) and class II with heights (5-10m) presented the greatest number of individuals and with the greatest basal area, class VII (timber trees between 60 and 100 cm).